PENGARUH KARAKTERISTIK INDIVIDU DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN DI DINAS PENANAMAN MODAL DAN PELAYANAN TERPADU SATU PINTU KABUPATEN BREBES - Medi Tri Purwanto (Jurnal Strategik, 2019)
ABSTRAK This study is entitled "The Effect of Individual Characteristics and Work Motivation on Employee Performance in the Office of Investment and Integrated Services One Door Brebes Regency". The formulation of the problem in this study are as follows: 1. Is there a significant influence between individual characteristics and work motivation partially on employee performance in the Investment Office and the One Stop Integrated Service at Brebes Regency? 2. Is there a significant influence between individual characteristics and work motivation simultaneously on employee performance in the Office Investment and Integrated Services One Door Brebes Regency? 3. Which is the more dominant influence between individual characteristics and work motivation on the performance of employees of the Office of Investment and Integrated Services at the one door of Brebes Regency? This research aims to: 1. To find out the significant influence between individual characteristics and work motivation partially on employee performance in the Investment Office and the One-Stop Integrated Service in Brebes Regency. 2. To find out the significant influence between individual characteristics and work motivation simultaneously on the performance of employees in the Investment Office and the One Stop Integrated Service Brebes Regency. 3. To find out there is a more dominant influence between individual characteristics and work motivation on the performance of the employees of the Investment Office and the One-stop Integrated Services in Brebes Regency. From the results of the research that has been carried out, the following conclusions can be drawn: 1. The results of the study of the influence of individual characteristic variables (X1) of Thitung - 0.547 0.025, this shows a negative and insignificant influence between individual characteristic variables (X1) with employee performance (Y). And for the results of work motivation variables of Tcount 7,741> Ttable 2,011, this means that Ho is rejected and Ha is accepted with a significance level of 0,000 F table 3.19, and the significance value of 0.000